Impact of Intercultural Sensitiv ity and Intercultural Communication Apprehension on Ethnocentrism: A Select Study of HEI of India - Bhargava, Megha; Panicker, Dr. Aneesya (The journal of contemporary issues in business and government, 2021)
In the global world where intercultural exchange of student group has become a common aspect wherein main cultures come in contact with each other in the journey of achieving motives like education, business jobs in global market etc. In such a scenario where people have to interact with diverse individuals they tend to treat their cultural norms and values superior to others. The existence of strong ethnocentrism does not allow smooth exchange of such values and culture. This study is an effort to understand the role of Intercultural sensitivity and intercultural communication apprehension on ethnocentric behavior of students of higher education institution (HEI) of India which receive a lot of foreign students every year to acquire higher education through various international schemes. The study will also identify the issues faced by students while interacting with the Indian students and students of different cultures in their day to day interaction while going through the journey of acquiring higher education.